HIV virological failure and drug resistance among injecting drug users receiving first-line ART in China. Issue 10 (15th October 2014) - Leng, Xuebing; Liang, Shujia; Ma, Yanling; Dong, Yonghui; Kan, Wei; Goan, Daniel; Hsi, Jenny H; Liao, Lingjie; Wang, Jing; He, Cui; Zhang, Heng; Xing, Hui; et al.
Abstract : Objective: To explore HIV virological failure and drug resistance among injecting drug users (IDUs) receiving first-line antiretroviral treatment (ART) in China. Design: A series of cross-sectional surveys from 2003 to 2012 from the Chinese National HIV Drug Resistance (HIVDR) Surveillance and Monitoring Network. Setting: China. Participants: Data were analysed by the Chinese National (HIVDR) Surveillance and Monitoring Network from 2003 to 2012. Demographic, ART and laboratory data (CD4+ cell count, viral load and drug resistance) were included. Factors associated with virological failure were identified by logistic regression analysis. Results: 929 of the 8556 individuals in the Chinese HIVDR database were IDUs receiving first-line ART. For these 929 IDUs, the median duration of treatment was 14 months (IQR 6.0–17.8). 193 of the 929 IDUs (20.8%) experienced virological failure (HIV viral load ≥1000 copies/mL). The prevalence of HIVDR among patients with virological failure was 38.9% (68/175). The proportion of patients with drug resistance to non-nucleoside reverse transcriptase inhibitor (NNRTIs), nucleoside reverse transcriptase inhibitor (NRTIs) and protease inhibitors (PIs) was 52.9%, 76.5% and 4.4%, respectively. Factors independently associated with virological failure include: ethnic minorities, junior high school education or less, farmers, self-reported missing doses in the past month, CD4 cell count at survey from 200 to 349 cells/mm 3 or from 0 to 199 cells/mm 3, and residence of Guangxi and Yunnan provinces. Conclusions: The proportion of virological failure was high among IDUs receiving first-line ART in China. However, better treatment outcomes were observed in Guangxi and Yunnan, which indicates the importance of ART education and adherence to intervention, especially for patients who are farmers, minorities or have a poor educational background.